Kinetics and functional consequences of BK channels activation by N-type Ca2+ channels in the dendrite of mouse neocortical layer-5 pyramidal neurons - Blömer, Laila Ananda; Giacalone, Elisabetta; Abbas, Fatima; Filipis, Luiza; Tegolo, Domenico; Migliore, Michele; Canepari, Marco (Frontiers in Cellular Neuroscience, 2024)
The back-propagation of an action potential (AP) from the axon/soma to the dendrites plays a central role in dendritic integration. This process involves an intricate orchestration of various ion channels, but a comprehensive understanding of the contribution of each channel type remains elusive. In this study, we leverage ultrafast membrane potential recordings (V m ) and Ca 2+ imaging techniques to shed light on the involvement of N-type voltage-gated Ca 2+ channels (VGCCs) in layer-5 neocortical pyramidal neurons' apical dendrites. We found a selective interaction between N-type VGCCs and large-conductance Ca 2+ -activated K + channels (BK CAKCs). Remarkably, we observe that BK CAKCs are activated within a mere 500 µs after the AP peak, preceding the peak of the Ca 2+ current triggered by the AP. Consequently, when N-type VGCCs are inhibited, the early broadening of the AP shape amplifies the activity of other VGCCs, leading to an augmented total Ca 2+ influx. A NEURON model, constructed to replicate and support these experimental results, reveals the critical coupling between N-type and BK channels. This study not only redefines the conventional role of N-type VGCCs as primarily involved in presynaptic neurotransmitter release but also establishes their distinct and essential function as activators of BK CAKCs in neuronal dendrites. Furthermore, our results provide original functional validation of a physical interaction between Ca 2+ and K + channels, elucidated through ultrafast kinetic reconstruction. This insight enhances our understanding of the intricate mechanisms governing neuronal signaling and may have far-reaching implications in the field.